Bodily Experience and Visual Metaphor in Two Swedish Trans Graphic Narratives. Issue 1 (1st March 2022) - Ernst, Nina
Abstract: This article examines how transgender themes are conveyed in two Swedish graphic narratives. Olivia Skoglund's debut graphic memoir, Nästan i mål! En komisk transition [Almost there: A comical transition] (2020) follows Olivia who navigates as a trans woman through a clueless cis society, while Elias Ericson's graphic novel Diana & Charlie (2021) depicts the relationship between two transgender friends and their struggle to find emotional stability in a heteronormative society. Drawing on Elisabeth El Rafaie's visual metaphor theory of pictorial, spatial and stylistic metaphors, it is argued that both Skoglund and Ericson place bodily experience, appearance, and perception at the centre of their concerns of being transgender, conveying the struggle for gender recognition as well as showing the misgendering of trans people by society.